Perbandingan Analisis Decline Curve antara Metode Trial Error dan Decline Type Curve Matching Untuk Menentukan Cadangan Minyak Sisa - Guntur Setiawan (Journal of Earth Energy Engineering, 2016)
Decline curve analysis often used to determine remaning reserves in a reservoir. To analyze with this method, the decline type curve from production period (trend) must be known. To determine decline type curve, in this paper will use two methods there are: trial error & x2 chisquare test and decline type curve matching. Both of methods have different way to determine decline type curve. Trial error done by making tabulation and calculation, while decline type curve matching done by overlay. The calculation are aimed to determine decline type curve, Remaining Reserves (RR) and Estimate Ultimate Recovery (EUR). Analysis done by taking sample of data well X which is a new well produced since September 2013 till the last data is Febuary 2016. First step of this study done by making type curve from equations and assumptionin literature then plot production rate vs time and choose production period (trend) to be analyzed. After that, determine decline type curve by trial error and decline type curve matching and do forecast until get remaining reserves and estimated ultimate recovery if economic limit rate production known. From calculation of both methods, resulted exponential decline type curve. For the error method obtained RR 41322,3 STB and EUR 240328,9 STB, while for decline type curve matching obtained RR 40534,2 STB and EUR 239540,8 STB